EMERGING TECHNOLOGIES IN TELEVISION BROADCASTING: CHANGES IN VISUAL PRESENTATION OF ODIA REGIONAL NEWS CHANNELS IN INDIA - Dr. Fakira Mohan Nahak (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Change is the unchangeable law of nature. This notion is applicable for all the developing fields of the universe. When we think of advancements in television broadcast technology, it is a kind of evolution that is taking place continuously in a progressive pace. The days of terrestrial transmission and linear video editing are obsolete now. Broadcasters do not solely depend on DSNG Vans or Outdoor Broadcasting vans to cover a live event. The digital revolution and developments in mobile internet as well as OTT (Over the Top) applications have made the live broadcasting process easy. Inaccessible remote areas have become accessible only after the invention of these mobile technologies. Similarly in visual editing technology has seen tremendous changes in last two decades. With the move from liner editing to digital non-linear editing the editing process has seen the sea change. This has helped the television industry to grow exponentially. Not only this, the user friendly technology has helped the TV professionals in making them multi-tasking. In this study the researcher has tried to observe the progress of television broadcasting in last two decades. Used discussion method and talked to different senior broadcasters to know the progress. To make the study more focused the researcher has taken Odia regional television channels as the area of study. It was found that the technological advancement has not only helped the broadcaster but also the receiver or the viewer in making and accessing quality content. It has helped to bring significant change in the visual presentation of the television channels.